Acute hyperkinetic movement disorders in Italian paediatric emergency departments. Issue 8 (8th March 2018) - Raucci, Umberto; Parisi, Pasquale; Vanacore, Nicola; Garone, Giacomo; Bondone, Claudia; Palmieri, Antonella; Calistri, Lucia; Suppiej, Agnese; Falsaperla, Raffaele; Capuano, Alessandro; Ferro, Valentina; Urbino, Antonio Francesco; et al.
Abstract : Introduction: Limited data exist on epidemiology, clinical presentation and management of acute hyperkinetic movement disorders (AHMD) in paediatric emergency departments (pED). Methods: We retrospectively analysed a case series of 256 children (aged 2 months to 17 years) presenting with AHMD to the pEDs of six Italian tertiary care hospitals over a 2-year period (January 2012 to December 2013). Results: The most common type of AHMD was tics (44.5%), followed by tremors (21.1%), chorea (13.7%), dystonia (10.2%), myoclonus (6.3%) and stereotypies (4.3%). Neuropsychiatric disorders (including tic disorders, psychogenic movement disorders and idiopathic stereotypies) were the most represented cause (51.2%). Inflammatory conditions (infectious and immune-mediated neurological disorders) accounted for 17.6% of the cases whereas non-inflammatory disorders (including drug-induced AHMDs, genetic/metabolic diseases, paroxysmal non-epileptic movements and idiopathic AHMDs) accounted for 31.2%. Neuropsychiatric disorders prevailed among preschoolers and schoolers (51.9% and 25.2%, respectively), non-inflammatory disorders were more frequent in infants and toddlers (63.8%), whereas inflammatory conditions were more often encountered among schoolers (73.3%). In 5 out of 36 Sydenham's chorea (SC) cases, tics were the presentation symptom on admission to emergency department (ED), highlighting the difficulties in early diagnosis of SC. Inflammatory disorders were associated with a longer hospital stay and a greater need of neuroimaging test compared with other disorders. Conclusions: This study provides the first large sample of paediatric patients presenting to the ED for AHMDs, helping to elucidate the epidemiology, aetiology and clinical presentation of these disorders.